Heat-Dissipation Performance of Nanocomposite Phase-Change Materials in a Twin-Heat-Source System - Yanxin Li; Jin Wang; Li Yang; Bengt Sundén (Fluids, 2020)
In this paper, pure paraffin was mixed with CuO (high thermal conductivity) and Span-80 (as a dispersant). The CuO/paraffin nanocomposite phase-change materials (PCMs) were synthesized with mass fractions of 0.3%, 0.6%, and 1.2%, by a two-step method. Heat-transfer characteristics of the heat-pipe–PCMs module and effects of fan power and heating power on the performance of the cooling module in a twin-heat-source system were studied. For two heat sources under 10 W–10 W (heat source 1 with a power of 10 W and heat source 2 with a power of 10 W), the paraffin wax decreases the evaporator temperature by 14.4%, compared with cases without PCMs.